Literatur Review Kepemimpinan Etis - Aam Rachmat Mulyana; Ade Sobandi; Budi Santoso (Ekonomis: Journal of Economics and Business, 2023)
Ethical leadership as a process helps connect the ethical elements of various leadership theories. This research is the result of a literature riviu of various studies and theories that can support leadership theory. Three processes will be explained here starting from conceptualization, definition and steps in the process of ethical leadership in this study, namely conceptualization, definition, steps of the ethical leadership process. Leadership styles according to several sources of experts have different meanings so that they have positive and negative sides.